2004 IEEE International Conference on Communications (IEEE Cat. No.04CH37577) 2004
DOI: 10.1109/icc.2004.1313353
|View full text |Cite
|
Sign up to set email alerts
|

A recursive, explicit and fair method to efficiently and fairly adjust TCP windows in satellite networks

Abstract: As originally specified, TCP did not perform well over satellite network systems, systems known with their rapidly time-varying network topologies. This paper addresses some vexing attributes that impair TCP performance in LEO satellite networks. The paper proposes a scheme that allows satellite systems to automatically adapt to the number of active TCP flows, the free buffer size and the bandwidth-delay product of the network. The proposed scheme controls the efficiency of the system by matching the aggregate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The figure demonsuates that for lower bit error rates, the REFWA and REFWA Plus scheme performs similarly and achieves the highest fairness (highest values of fairness index). This performance is consistent with the simulation results presented in [l] [ 2 ] . It is observed that although TCP WestwoodNR and TCP Newreno achieve relatively goad link utilization for low bit error rates (Fig.3(a)), they fail io sustain a fair service.…”
Section: B Sinrulation Resultssupporting
confidence: 93%
“…The figure demonsuates that for lower bit error rates, the REFWA and REFWA Plus scheme performs similarly and achieves the highest fairness (highest values of fairness index). This performance is consistent with the simulation results presented in [l] [ 2 ] . It is observed that although TCP WestwoodNR and TCP Newreno achieve relatively goad link utilization for low bit error rates (Fig.3(a)), they fail io sustain a fair service.…”
Section: B Sinrulation Resultssupporting
confidence: 93%
“…Use of a large number of satellites provides certainly more flexibility. It, however, leads to complex dynamic routing and mobility management issues caused by frequent handover occurrences [11,12]. Furthermore, LEO or MEO satellites can be used for only a short life span.…”
mentioning
confidence: 99%